An American in Scotland [large type] - Connelly, Lucy (Connelly, Lucy. Scottish Isle mystery, 2023)
"The small idyllic town of Sea Isle, Scotland, harbors some dark secrets, and Dr. Emilia McRoy is determined to uncover all of them-no matter what the diagnosis in this charming cozy, sure to enchant fans of Sheila Connolly and Charlene O'Connor. Sea Isle was supposed to be the fresh start Dr. Emilia McRoy dreamed of. Far from the busy emergency room across the Atlantic in Seattle, she hoped to settle down and begin this new chapter as a small-town doctor to the quirky residents who immediately welcomed her. When she stumbles across a dead body, she starts to think that she may not be as Scot free of the drama and intrigue as she initially thought. Emilia soon learns she has bigger issues at hand. It starts with realizing she'll work closely with the less than helpful local constable, Laird Ewan Campbell. Her luck continues when she discovers that part of her new responsibilities includes being the coroner for the very body she found. Finally, when the body goes missing before she can even begin the autopsy, Emilia must convince the townspeople that a crime did, in fact, occur. The deeper she digs into the picturesque town, the more suspicious she becomes. And then there are her sleep issues. It may be due to the ever-growing list of suspects, a number of threatening letters, or the surprise visitor who breaks into her house at night. But she's never backed down before, and she doesn't intend to start now. Someone doesn't want this doctor to treat the ailments of Sea Isle, but Emilia McRoy is determined to find the murderer before they kilt again"--